2004
DOI: 10.1142/s0219887804000216
|View full text |Cite
|
Sign up to set email alerts
|

Gribov Problem for Gauge Theories: A Pedagogical Introduction

Abstract: The functional-integral quantization of non-Abelian gauge theories is affected by the Gribov Their occurrence (lack of global cross-sections from the point of view of differential geometry) is called Gribov ambiguity, and is here presented within the framework of a global approach to quantum field theory. We first give a simple (standard) example for the SU (2) group and spherically symmetric potentials, then we discuss this phenomenon in general relativity, and recent developments, including lattice calculati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 51 publications
(79 reference statements)
0
26
0
Order By: Relevance
“…Naively, one could expect to completely avoid the Gribov problem by simply choosing algebraic gauge fixings like the axial gauge or the temporal gauge, which are free of Gribov copies. However, these choices have their own, and even worse, problems 1 (for a detailed reviews see [4] [5]). Here it is just worth mentioning one serious issue: any loop computation in the algebraic gauge-fixings mentioned above are very difficult already beyond two-loop.…”
Section: Introductionmentioning
confidence: 99%
“…Naively, one could expect to completely avoid the Gribov problem by simply choosing algebraic gauge fixings like the axial gauge or the temporal gauge, which are free of Gribov copies. However, these choices have their own, and even worse, problems 1 (for a detailed reviews see [4] [5]). Here it is just worth mentioning one serious issue: any loop computation in the algebraic gauge-fixings mentioned above are very difficult already beyond two-loop.…”
Section: Introductionmentioning
confidence: 99%
“…However, beyond perturbation theory, gauge conditions like the Landau-gauge condition (6) have no longer a unique solution for a given configuration. There are several explicit examples illustrating this fact [18,[45][46][47][48]. Such independent solutions are called Gribov copies, and the associated ambiguity of the gauge condition is termed the Gribov-Singer ambiguity [18,19].…”
Section: Non-perturbative Gauge-fixing and Gribov Copiesmentioning
confidence: 99%
“…In the perturbative expansion of a renormalizable theory, like Yang-Mills theory, it can be shown that this is possible with a finite number of independent renormalization constants. For covariant gauges, like the Landau gauge, this is equivalent to multiplying correlation functions by appropriate chosen renormalization factors 47 , at least as long as no matter fields are involved. If this is also possible beyond perturbation theory has not yet been proven, though no evidence to the contrary exists.…”
Section: Renormalizationmentioning
confidence: 99%
“…In the nonperturbative regime, the Faddeev-Popov trick for covariant gauges does therefore not correspond to inserting a ''1'' into the functional integral, instead one inserts a ''0'', making the functional integral ill-defined, [66]. In gravity, the Gribov problem has been discussed in [67][68][69]. We observe an interesting alteration to the standard problem in our setting: At locations in metric configuration space where the simple FP determinant would be zero, the additional terms in the ghost action, which will in general depend on the background metric and the matter fields, need not be zero.…”
Section: Gribov Problem and Nonperturbative Structure Of The Ghostmentioning
confidence: 99%